Meta-type wholly aromatic polyamide fiber and fabric using the same

By incorporating stilbene compounds and titanium oxide into meta-type all-aromatic polyamide fibers, the issue of yellowish hue is addressed, resulting in fibers with improved whiteness and brightness, enhancing their aesthetic and visual properties.

JP2025050502APending Publication Date: 2025-04-04TEIJIN LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023159334
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Conventional meta-type all-aromatic polyamide fibers exhibit a yellowish hue, which limits their aesthetic and visual properties, and existing dyeing methods fail to improve whiteness while maintaining physical properties.

Method used

Incorporating stilbene compounds and titanium oxide within specific concentration ranges into the meta-type all-aromatic polyamide fibers, resulting in a whiteness value of 75 to 100 and a brightness value of 80 to 100, thereby enhancing the fibers' aesthetic and visual properties.

Benefits of technology

The proposed solution achieves significant improvement in whiteness and brightness of meta-type all-aromatic polyamide fibers, resulting in a white, flame-retardant fabric with enhanced aesthetic and visual properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025050502000001
    Figure 2025050502000001
  • Figure 2025050502000002
    Figure 2025050502000002
Patent Text Reader

Abstract

To provide a meta-type wholly aromatic polyamide fiber which is reduced in yellowish coloration of a polymer itself, is excellent in aesthetic property and visual property, and has high whiteness, and to provide a fabric made of the same.SOLUTION: A fabric is obtained by using a meta-type wholly aromatic polyamide fiber containing 0.001 wt.% or more and 0.05 wt.% or less of a stilbene compound having a decomposition temperature of 300°C and 1.0 wt.% or more and 10.0 wt.% or less of titanium dioxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a meta-type wholly aromatic polyamide fiber having excellent whiteness. [Background technology]

[0002] It has been well known that fully aromatic polyamides produced from aromatic diamines and aromatic dicarboxylic acid dihalides have excellent heat resistance and flame retardancy. It is also well known that these fully aromatic polyamides are soluble in amide polar solvents, and that the polymer solution in which the fully aromatic polyamide is dissolved in the solvent can be made into fibers by methods such as dry spinning, wet spinning, and semi-dry and semi-wet spinning. Among these fully aromatic polyamides, fibers of meta-type fully aromatic polyamides (sometimes called "meta-aramids"), represented by polymetaphenylene isophthalamide, are particularly useful as heat-resistant and flame-retardant fibers, and are used in fields where these properties are exhibited, such as industrial applications such as filters and electronic components, and disaster prevention and safety clothing applications such as protective clothing, where heat resistance, flame retardancy, and flame resistance are important. Recently, applications are rapidly expanding not only to industrial applications, but also to fields requiring aesthetics and visual appeal, such as bedding, clothing, and interiors. However, the hue of conventional meta-type wholly aromatic polyamide fibers is slightly yellowish, and improvements in aesthetics and visibility are desired.

[0003] In order to improve the yellowish color of meta-type wholly aromatic polyamide fibers (to give them whiteness), a dyeing method using a fluorescent dye has been proposed (Patent Document 1). However, meta-type wholly aromatic polyamide fibers for dyeing have a problem of low physical properties, and the method using a fluorescent dye has a problem of poor whiteness of the fibers. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2011-252247 A Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention has been made in view of the above-mentioned background art, and an object of the present invention is to provide a meta-type wholly aromatic polyamide fiber having excellent whiteness. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve the above problems and have found that by incorporating a stilbene compound and titanium oxide in specific ranges, meta-type wholly aromatic polyamide fibers having excellent whiteness can be obtained, thereby completing the present invention.

[0007] That is, the present invention has the following configuration. [Section 1] The present invention relates to a meta-type wholly aromatic polyamide fiber, characterized in that it contains, based on the weight of the meta-type wholly aromatic polyamide fiber, 0.001 wt% or more and less than 0.05 wt% of a stilbene compound having a decomposition temperature of 300°C or more, and 1.0 wt% or more and 10.0 wt% or less of titanium oxide.

[0008] Furthermore, the present invention also includes the following configurations as preferred embodiments. [Section 2] Item 2. A meta-type wholly aromatic polyamide fiber according to Item 1, having a Whiteness value of 75 to 100 according to ASTM E313-05 (D65). [Section 3] Item 3. The meta-type wholly aromatic polyamide fiber according to Item 1 or 2, having a brightness value of 80 to 100 in accordance with ISO2470-1. [Section 4] 4. The meta-type wholly aromatic polyamide fiber according to any one of items 1 to 3, which contains titanium oxide having an average particle size of 0.1 μm or more and 2.0 μm or less. [Section 5] Item 5. A fabric comprising the meta-type wholly aromatic polyamide fiber according to any one of items 1 to 4. Effect of the Invention

[0009] The meta-type wholly aromatic polyamide fiber of the present invention is a fiber with improved whiteness, and therefore, when a fabric is produced using the fiber as a constituent component, the yellowish tinge inherent to the polymer itself is improved, and a white flame-retardant fabric with excellent aesthetics and visibility can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] <Meta-type wholly aromatic polyamide> [Structure of meta-type wholly aromatic polyamide] The meta-type wholly aromatic polyamide of the present invention is composed of a meta-type aromatic diamine component and a meta-type aromatic dicarboxylic acid component, and may be copolymerized with other copolymerization components such as para-type within a range that does not impair the object of the present invention.

[0011] From the viewpoints of mechanical properties and heat resistance, meta-type wholly aromatic polyamides mainly composed of metaphenylene isophthalamide units are particularly preferably used in the present invention. In meta-type wholly aromatic polyamides composed of metaphenylene isophthalamide units, the metaphenylene isophthalamide units preferably account for 90 mol % or more of all repeating units, more preferably 95 mol % or more, and particularly preferably 100 mol %.

[0012] [Raw material for meta-type wholly aromatic polyamide] (Meta-type aromatic diamine component) Examples of the meta-type aromatic diamine component include metaphenylenediamine, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl sulfone, and derivatives thereof having a substituent such as halogen or an alkyl group having 1 to 3 carbon atoms on the aromatic ring, such as 2,4-toluylenediamine, 2,6-toluylenediamine, 2,4-diaminochlorobenzene, 2,6-diaminochlorobenzene, etc. Among these, only metaphenylenediamine or a mixed diamine containing 70 mol % or more of metaphenylenediamine is preferable.

[0013] (Meta-type aromatic dicarboxylic acid component) Examples of the meta-type wholly aromatic dicarboxylic acid component include meta-type aromatic dicarboxylic acid halides. Examples of the meta-type aromatic dicarboxylic acid halides include isophthalic acid halides such as isophthalic acid chloride and isophthalic acid bromide, and derivatives thereof having a substituent such as halogen or an alkoxy group having 1 to 3 carbon atoms on the aromatic ring, such as 3-chloroisophthalic acid chloride and 3-methoxyisophthalic acid chloride. Among them, it is preferable to use only isophthalic acid chloride or the above-mentioned mixed carboxylic acid halide containing 70 mol % or more of isophthalic acid chloride.

[0014] (Copolymerization component) Examples of copolymerization components that can be used other than the meta-type aromatic diamine component and meta-type aromatic dicarboxylic acid component include, for example, aromatic diamines such as paraphenylenediamine, 2,5-diaminochlorobenzene, 2,5-diaminobromobenzene, benzene derivatives such as aminoanisidine, 1,5-naphthylenediamine, 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylketone, 4,4'-diaminodiphenylamine, 4,4'-diaminodiphenylmethane, etc. On the other hand, examples of aromatic dicarboxylic acid components include terephthalic acid chloride, 1,4-naphthalenedicarboxylic acid chloride, 2,6-naphthalenedicarboxylic acid chloride, 4,4'-biphenyldicarboxylic acid chloride, 4,4'-diphenyletherdicarboxylic acid chloride, etc.

[0015] The copolymerization ratio of these copolymerization components is preferably 20 mol % or less based on the total acid components of the polyamide, since if it is too high, the properties of the meta-type wholly aromatic polyamide tend to deteriorate. As described above, a particularly suitable meta-type wholly aromatic polyamide is a polyamide in which 90 mol % or more of the total repeating units are metaphenylene isophthalamide units, and among them, polymetaphenylene isophthalamide is particularly preferred. The degree of polymerization of such meta-type wholly aromatic polyamide was measured by the following procedure: The intrinsic viscosity (IV) measured by this method is suitably in the range of 1.3 to 3.0.

[0016] [Method for producing meta-type wholly aromatic polyamide] The method for producing a meta-type wholly aromatic polyamide is not particularly limited. For example, Solution polymerization of a diamine type aromatic diamine component and a meta type aromatic dicarboxylic acid chloride component The polymerizable composition can be produced by, for example, polymerization or interfacial polymerization.

[0017] The meta-type wholly aromatic polyamide fiber of the present invention contains both a stilbene compound and titanium oxide. If only one of them is used, the desired whiteness, specifically a whiteness that combines high whiteness and brightness properties, cannot be obtained. The method of adding the stilbene compound and titanium oxide to the wholly aromatic polyamide is not particularly limited, but adding them to the spinning solution (meta-type wholly aromatic polyamide polymer solution) for forming the fiber is preferable because it is possible to prepare a uniform spinning solution containing the meta-type wholly aromatic polyamide, the stilbene compound, and titanium oxide.

[0018] [Stilbene Compounds] The stilbene compound used in the present invention is used to enhance whiteness, and various compounds made from stilbene as a raw material are commercially available. In the present invention, these commercially available products can be preferably used, and compounds commercially available as dyes or fluorescent whitening agents can also be used.

[0019] (Blend amount) The content of the stilbene compound used in the present invention is in the range of 0.001wt% or more and less than 0.05wt%, preferably 0.002wt% or more and less than 0.02wt% based on the total weight of the meta-type wholly aromatic polyamide fiber. More preferably, it is in the range of 0.003wt% or more and less than 0.01wt%. If the content of the stilbene compound is less than 0.001wt%, the whiteness of the obtained fiber is insufficient. On the other hand, if the content of the stilbene compound exceeds 0.05wt%, the yellowish color of the stilbene compound itself becomes stronger, and the whiteness decreases.

[0020] (Melting Point) The decomposition temperature of the stilbene compound used in the present invention is 300° C. or higher, and preferably 350° C. or higher. If the decomposition temperature of the stilbene compound is lower than 300° C., the stilbene compound decomposes, and the whiteness of the meta-type wholly aromatic polyamide fiber decreases.

[0021] [Titanium oxide] As the titanium oxide for use in the present invention, various types are commercially available, and in the present invention, those commercially available products can be preferably used, and titanium oxide used as a pigment is more preferable.

[0022] (Blend amount) The content of titanium oxide used in the present invention is 1.0wt% or more and 10.0wt% or less based on the total weight of the meta-type wholly aromatic polyamide fiber. It is preferably in the range of 2.0wt% or more and 9.0wt% or less. It is more preferably in the range of 3.0wt% or more and 8.0wt% or less. If it is less than 1.0wt%, the whiteness of the obtained fiber is insufficient. On the other hand, if it exceeds 10.0wt%, the amount of polymer as a matrix is ​​significantly small, resulting in a decrease in physical properties and instability in the manufacturing process.

[0023] (Average particle size) The average particle size of titanium oxide used in the present invention is in the range of 0.1 μm to 2.0 μm. It is preferably 0.2 to 1.0 μm. If the average particle size of titanium oxide is less than 0.1 μm, the hiding power may be small and the whiteness may be reduced. On the other hand, if the average particle size of titanium oxide is more than 2.0 μm, the physical properties may be deteriorated and the manufacturing process may become unstable.

[0024] (Crystal structure) The crystal structure of titanium oxide used in the present invention is not particularly limited. The crystal structure includes anatase type (tetragonal crystal), rutile type (tetragonal crystal, see figure), and brookite type (orthorhombic crystal). Rutile type is preferable because it improves the hiding rate, and therefore has a higher whiteness than anatase type when the content is the same.

[0025] <Method of manufacturing meta-type wholly aromatic polyamide fiber> The meta-type wholly aromatic polyamide fiber of the present invention is produced by preparing a spinning solution (polymer dope) containing the meta-type wholly aromatic polyamide, a stilbene compound, and titanium oxide using the meta-type wholly aromatic polyamide obtained by the above-mentioned production method, and carrying out a spinning / coagulation step, a wet heat drawing step, and a relaxation heat treatment step.

[0026] [Spinning solution preparation process] In the spinning solution preparation step, meta-type wholly aromatic polyamide is dissolved in an amide solvent, and a stilbene compound and titanium oxide are further added to prepare a spinning solution (meta-type wholly aromatic polyamide polymer solution). In preparing the spinning solution, an amide solvent is usually used, and examples of the amide solvent that can be used include N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), and dimethylacetamide (DMAc). Among these, it is preferable to use NMP or DMAc from the viewpoints of solubility and handling safety.

[0027] The solution concentration may be appropriately selected from the viewpoints of the coagulation rate in the subsequent spinning / coagulation process and the solubility of the polymer. For example, when the polymer is polymetaphenylene isophthalamide and the solvent is NMP, it is usually preferable to set the concentration in the range of 10 to 30 mass %.

[0028] [Spinning and coagulation process] In the spinning and coagulation step, the spinning solution (meta-type wholly aromatic polyamide polymer solution) obtained above is spun into a coagulation solution and coagulated to obtain a fibrous material.

[0029] The spinning device is not particularly limited, and a conventionally known wet spinning device can be used. In addition, the number of spinning holes, the arrangement, the hole shape, etc. of the spinneret do not need to be particularly limited as long as it can perform stable wet spinning. For example, a multi-hole spinneret for staple fibers having 100 to 30,000 holes and a spinning hole diameter of 0.05 to 0.2 mm may be used. The temperature of the spinning solution (meta-type wholly aromatic polyamide polymer solution) when it is spun out from the spinneret is suitably in the range of 10 to 90°C.

[0030] The coagulation bath for obtaining the fibers used in the present invention is substantially composed of an aqueous solution consisting of two components, an amide solvent and water. However, since inorganic salts such as calcium chloride and calcium hydroxide are extracted from the polymer solution, the coagulation liquid actually contains a small amount of these salts. The amide solvent in the coagulation bath composition is not particularly limited as long as it dissolves the meta-type wholly aromatic polyamide and is well miscible with water, but N-methyl-2-pyrrolidone, dimethylacetamide, dimethylformamide, dimethylimidazolidinone, etc. can be preferably used.

[0031] The optimal mixing ratio of the amide solvent to water varies slightly depending on the conditions of the polymer solution, but in general, it is preferable that the ratio of the amide solvent is in the range of 40% by mass to 60% by mass with respect to the entire aqueous solution. Under conditions below this range, very large voids are likely to occur in the coagulated fiber, which is likely to cause subsequent fiber breakage. On the other hand, under conditions above this range, coagulation does not proceed and fusion of the fibers is likely to occur.

[0032] The temperature of the coagulation bath is closely related to the composition of the coagulation liquid, but in general, it is preferable to set the temperature high in order to prevent the formation of large bubble-like voids called fingers in the resulting fiber. However, if the concentration of the coagulation liquid is relatively high, the fibers will fuse together violently if the temperature is too high. Therefore, the suitable temperature range of the coagulation bath is 20 to 70°C, and more preferably 25 to 60°C.

[0033] The immersion time of the fibrous material (filament) in the coagulation bath is preferably in the range of 1.5 to 30 seconds. If the immersion time is less than 1.5 seconds, the formation of the fibrous material is insufficient and thread breakage occurs. On the other hand, if the immersion time exceeds 30 seconds, the productivity decreases, which is not preferable.

[0034] [Moist heat stretching process] In the wet heat drawing step, a fiber bundle consisting of a fibrous material (filament) obtained by coagulation in a coagulation bath is drawn in one stage under wet heat, such as in boiling water or high-temperature steam.

[0035] The stretch ratio in the wet heat stretching step is preferably 2.0 to 4.5 times, more preferably in the range of 2.2 to 4.0 times. By carrying out the wet heat single-stage stretching, the obtained fiber can have high strength. When the wet heat single-stage stretching ratio in the wet heat stretching step is less than 2.0 times, the stretching is insufficient, and high strength may not be exhibited. On the other hand, when the wet heat single-stage stretching ratio exceeds 4.5 times, the stretching is excessive, and uniform performance may not be exhibited. The temperature during wet heat stretching is usually 50 to 100°C, and preferably 80 to 100°C.

[0036] [Hot stretching process] In the hot drawing step, the fibers that have been subjected to one-stage drawing in the wet heat drawing step are subjected to a hot drawing treatment.

[0037] The stretch ratio during heat treatment is preferably in the range of 1.2 to 2.0 times, and more preferably in the range of 1.5 to 1.8 times. When heat-stretching is performed at less than 1.2 times, excellent strength may not be achieved. On the other hand, when heat-stretching is performed at more than 2.0 times, single yarn breakage may occur, leading to deterioration of physical properties and quality. The temperature during hot stretching is usually 280 to 350°C, and preferably 300 to 340°C.

[0038] [Physical properties of meta-type fully aromatic polyamide fibers] [Whiteness] The whiteness of the meta-type wholly aromatic polyamide fiber of the present invention, as determined in accordance with ASTM E313-05 (D65), is preferably 75 to 100, more preferably 80 to 100. If the whiteness value is less than 75, the fiber lacks whiteness and is not preferable in terms of aesthetics and visibility when used for firefighting clothing, flame-retardant work clothing, etc.

[0039] [Brightness] The brightness of the meta-type wholly aromatic polyamide fiber of the present invention, as measured in accordance with ISO2470-1, is preferably 80 to 100, and more preferably 85 to 100. If the brightness is less than 80, it is perceived as yellowing when used in firefighting clothing, flame-retardant work clothing, etc., and is therefore undesirable from the standpoints of aesthetics and visibility. EXAMPLES

[0040] The present invention will be described in more detail with reference to the following examples and comparative examples. However, these examples and comparative examples are provided to aid in understanding the present invention, and are not intended to limit the scope of the present invention.

[0041] <Measurement and evaluation method> In the examples and comparative examples, the following items were measured and evaluated by the following methods. (1) Average particle size of titanium dioxide The particle size of the particles was measured according to JIS Z 8825. Specifically, a Microtrac MT3000 from Microtrac Bell Corporation was used, and measurements were performed by the laser diffraction / scattering method under the following conditions: laser wavelength: 780 nm, measurement time: 30 sec, number of measurements: 2, transmittance: reflection, solvent: ion-exchanged water, solvent refractive index: 1.33. (2) Whiteness The whiteness of the meta-type wholly aromatic polyamide fiber was measured using a spectrophotometer SD7000 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with ASTM E313-05 (D65). (3)Brightness The brightness of meta-type wholly aromatic polyamide fibers was measured using a spectrophotometer SD7000 (manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with ISO2470-1.

[0042] <Example 1> A stilbene compound (product name NIKKAFLUOR SB conc., Nippon Chemical Industry Co., Ltd.) was added at 0.005 wt% relative to the polymer, and titanium oxide (product name CR-60, Ishihara Sangyo Kaisha, Ltd.) was added at 5.0 wt% to a 21 mass percent N-methyl-2-pyrrolidone solution of meta-type wholly aromatic polyamide polymerized from metaphenylenediamine and isophthalic acid chloride, to prepare a spinning solution.

[0043] The spinning solution was then extruded through a nozzle with 100 holes and a hole diameter of 0.07 mm, and extruded at a speed of 5.0 m / min into an inorganic salt bath mainly composed of calcium chloride, where it was coagulated. After washing with water, it was subjected to a one-stage wet heat stretching of 2.4 times in boiling water, and then to a hot stretching of 1.8 times on a hot plate at 330°C. Various physical properties of the obtained fiber were measured. The results are shown in Table 1.

[0044] <Example 2> The same procedure as in Example 1 was carried out, except that the stilbene compound was added in an amount of 0.001 wt % relative to the polymer. The results are shown in Table 1.

[0045] <Example 3> The same procedure as in Example 1 was carried out, except that the stilbene compound was added in an amount of 0.02 wt % relative to the polymer. The results are shown in Table 1.

[0046] <Example 4> The same procedure as in Example 1 was carried out, except that titanium oxide was added in an amount of 2.0 wt % relative to the polymer. The results are shown in Table 1.

[0047] <Example 5> The same procedure as in Example 1 was carried out, except that titanium oxide was added in an amount of 10.0 wt % relative to the polymer. The results are shown in Table 1.

[0048] <Comparative Example 1> The stilbene compound and titanium oxide were not added, but otherwise the same method as in Example 1 was carried out. The obtained results are shown in Table 2. When the stilbene compound and titanium oxide were not added, the desired whiteness and brightness values ​​were not obtained.

[0049] <Comparative Example 2> The same procedure as in Example 1 was carried out, except that the stilbene compound was added in an amount of 0.0005 wt % relative to the polymer. The results are shown in Table 2. When the stilbene compound was 0.0005 wt % relative to the polymer, the desired whiteness value was not obtained.

[0050] <Comparative Example 3> The same procedure as in Example 1 was carried out, except that the stilbene compound was added in an amount of 0.1 wt % relative to the polymer. The results are shown in Table 2. When the stilbene compound was 0.1 wt % relative to the polymer, the desired whiteness value was not obtained.

[0051] <Comparative Example 4> Except for adding titanium oxide in an amount of 0.5 wt % relative to the polymer, the same method as in Example 1 was carried out. The results are shown in Table 2. When the titanium oxide was 0.5 wt% relative to the polymer, the desired whiteness value was not obtained.

[0052] <Comparative Example 5> The same procedure as in Example 1 was carried out, except that titanium oxide was added in an amount of 15.0 wt % relative to the polymer. The results are shown in Table 2. When the titanium oxide content was 15.0 wt % relative to the polymer, fiber breakage increased during the wet heat drawing process and the hot drawing process, and fibers could not be obtained.

[0053] <Comparative Example 6> The same method as in Example 5 was carried out except that the average particle size of titanium oxide was 0.05 μm. The results are shown in Table 2. When the average particle size of titanium oxide was 0.05 μm, the desired whiteness value was not obtained.

[0054] <Comparative Example 7> Except for changing the average particle size of titanium oxide to 3.0 μm, the same method as in Example 1 was carried out. The obtained results are shown in Table 2. When the average particle size of titanium oxide was 3.0 μm, fiber breakage increased during the wet heat drawing step and the hot drawing step, and fibers could not be obtained.

[0055] [Table 1]

[0056] [Table 2]

Claims

1. A meta-type wholly aromatic polyamide fiber, characterized by containing, based on the weight of the meta-type wholly aromatic polyamide fiber, 0.001 wt % or more and less than 0.05 wt % of a stilbene compound having a decomposition temperature of 300° C. or more and 1.0 wt % or less of titanium oxide.

2. 2. The meta-type wholly aromatic polyamide fiber according to claim 1, which has a Whiteness value of 75 to 100 according to ASTM E313-05 (D65).

3. 2. The meta-type wholly aromatic polyamide fiber according to claim 1, which has a brightness value of 80 to 100 according to ISO 2470-1.

4. 2. The meta-type wholly aromatic polyamide fiber according to claim 1, which contains titanium oxide having an average particle size of 0.1 μm or more and 2.0 μm or less.

5. A fabric comprising the meta-type wholly aromatic polyamide fiber according to claim 1.

Citation Information

Patent Citations

  • Aramid fiber with improved brightness and producing method of the same

    JP2011252247A